National Identity and Migration Policy Dynamics: Analysing the Effect of Swedish National Identity on Its Granting Asylum Policy to Syrian Refugees in 2013 - Suryani, Desak Sinta Putu; Cangara, Abdul Razaq (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2022)
The Syrian conflict in 2011 has inevitably led to the massive forced migration of asylum seekers and refugees. Most of them fled to neighbouring and several countries in Europe. As a result of the European Union (EU) 's open border policy, their influx into Europe was reckoned a problem for many European countries due to increasing crimes and threats to its members' national security. Some European Union countries chose to be cautious by refusing or only providing financial assistance. Contrastingly, as an EU member state, Sweden received thousands of Syrian refugees until 2013. On October 3, 2013, the Swedish government announced an asylum policy of guaranteed housing provision and the right to bring families to Syrian asylum seekers until they obtain UNHCR refugee status. Such granting asylum policy to Syrian refugees shows differences in the identity of social security construction both in the society and its decision-makers compared to other EU countries. This article exposes the identity influence on the Swedish government's decision to grant asylum to Syrian refugees in 2013. This article employs the "aspirational constructivism" theory by Anne Clunan, arguing that a state's policy is based on a national identity sourced from society's historical reflections and the political elite's future aspirations. This article finds that Swedish society's history experienced cultural homogenization, known as a multicultural country, and the ​​Social-Democracy and folkhemmet ("Home for the People") idea of the political elites resulted in the granting of asylum policy to Syrian refugees in October 2013.